PHONOLOGY ACQUISITION AT THE HOLOPHRASTIC STAGE - Sebastianus Menggo (Unika Santu Paulus Ruteng, 2017)
The aim of this preliminary research is to know and describe the phonology acquisition toward early childhood on 15 until 20 months age old in Santo Paulus Preschool, Singaraja, Bali which altogether 7 children. Purposive procedure was applied in this study. Then data were collected through observation, field note, and natural recorded when the respondents were playing and interacting each other in school park. Data collection were done during four days and only certain utterances of those respondents were recorded. The utterances recorded are expected to be representative of the whole 7 children’s phonology acquisition. Utterances repeated by students were recorded precisely by the researcher. The result showed that, children on 15 until 20 months old age generally have acquired vocal phonemes (u, i, e, o). Then, the structure of utterances by this age from easy to difficult phonemes. The distinction of phonem difficulty referenced to the how child articulated the total of distinction feature of each phonem. Vocal phonemes acquisition of 15 until 20 months age old have already completely acquired. There was no vocal phonem change or created a new vocal phonem. Meanwhile, consonant acquisition for the children of this stage, the researcher found that 4 children still have the problem of certain consonants such as r, s, k, j and t. The children articulated those phonemes were different from adult’s production but those differences indicated to the equality of semantic perspective with adult.